Ketimpangan Antar Wilayah & Hubungannya dengan Belanja Pemerintah: Studi di Indonesia - Marihot Nasution (Pusat Kajian Anggaran, 2020)
This study examines the development of inequality between regions in Indonesia from 2010-2019. Tests are carried out by grouping using Klassen's typology and measuring the value of inequality using the Williamson Index. In addition, the results of the inequality calculation are tested for correlation with government spending according to type, namely personnel expenditure, material expenditure, capital expenditure, subsidy expenditure, grant expenditure, social assistance expenditure, and transfers to the regions.The results showed that the Klassen typology categorized 2 provinces as developed and rapidly developing provinces/quadrant 1, namely DKI Jakarta and Riau Islands. Meanwhile, 8 provinces are included in the group of provinces that are categorized as underdeveloped (quadrant 3). For the group of provinces that are classified as developing with per capita income exceeding the average but with low growth and are in quadrant 4, there are 5 provinces and other provinces (19 provinces) are included in quadrant 2 where the growth is high but the GDP per capita is below the average. Meanwhile, the value of inequality as measured by the Williamson index during 2010-2019 is in the range of 0.70-0.76, which is close to number 1, meaning that Indonesia experiences high regional inequality. The results of the correlation testing for variations in the Williamson Index on variations in state expenditure show that personnel spending, goods spending, capital expenditures, and transfers to regions have a positive and significant relationship to the Williamson index. This proves that state spending is still not evenly distributed and still unable to lift regions with low growth.